A Second Thought on the Success-Breeds-Success Model: Comment on Iso-Ahola and Dotson (2014). Issue 1 (March 2015) - Avugos, Simcha; Bar-Eli, Michael
The notion that "success breeds success, and failure breeds failure" is a widely held belief applied by people to a variety of situations in everyday life. Initial success is assumed to generate confidence, which then increases the likelihood of success in subsequent trials. Repeated failures are expected to lead to diminished future accomplishments. One arena in which the apparent relationship between psychological factors and sequences of successes and failures has been tested is sport. Recently, Iso-Ahola and Dotson (2014) developed a model of psychological momentum (PM), and argued that the "hot hand" can be detected in sport (including games such as basketball) if the appropriate methodology and statistical tests are employed. This commentary examines their theoretical framework and conclusions, which seem to be rather conflicting in light of the evidence on the performance-enhancing effects of PM and the hot hand in sports. More specifically, we argue that their claims have received only limited support, suggesting that more solid empirical evidence is required to support the "success-breeds-success" principle and the conceptual framework of PM, at least as the sport arena is concerned.